A Comparative Study and Analysis on Conventional Solar PV Based DC-DC Converters and MPPT Techniques - Premkumar Manoharan; Karthick K; Sowmya R (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
As electricity demand escalated with supply, though there are lot of thermal power station, nuclear energy and other conventional power sources. Yet, there is exhaustion in the above assets and adding dangerous impacts to the atmospheric conditions.  The world searches for sustainable power source that it is normally accessible such as sun and wind. Apart from all the renewable energy resources, solar energy is readily harnessed for domestic application to meet demand. To increase the power conversion efficiency from the solar PV system it is better have a perfect DC to DC converters. The proposed outcome of this paper is to outline the DC to DC converter with MPPT algorithms to concentrate on extreme productivity at roof-top for solar PV application which decreases the cost of energy. In addition to that it also prevents panel miss matching at all environmental conditions for safer DC Voltage with flexible site design especially for domestic applications from the solar photovoltaic module. It is necessary to analyze the converters and MPPT algorithms under closed loop condition for the design and installation of solar PV system to the load or to the grid. This review summarizes few DC to DC converter topologies, maximum power point tracking algorithm and also paid attention on the advantages and disadvantages of these algorithms and topologies.